Review of phase change emulsions (PCMEs) and their applications in HVAC systems - Shao, Jingjing; Darkwa, Jo; Kokogiannakis, Georgios (Elsevier, 2015)
Phase change material emulsions (PCMEs) are multifunctional fluids consisting of phase change materials (PCMs) and carrier fluids. PCMEs could be potential candidates as heat transfer media in heating, ventilation and air conditioning (HVAC) systems. This is mainly because PCME could take advantage of its high heat capacity to reduce flow rate and thus saving pumping power whilst delivering the same amount of cooling effect. PCME can also simultaneously act as cold storage to shift peak-load to off-peak time and improve the COP of systems. However, the optimum design of integrated system requires a good understanding of flow behaviour and heat transfer characteristics of PCMEs. In this paper, comprehensive reviews of their thermo-physical properties and potential applications as thermal energy storage and as alternative heat transfer fluids in air conditioning systems have been carried out to establish their limitations for future research.